2009
DOI: 10.2353/ajpath.2009.080612
|View full text |Cite
|
Sign up to set email alerts
|

Semicarbazide-Sensitive Amine Oxidase/Vascular Adhesion Protein-1 Deficiency Reduces Leukocyte Infiltration into Adipose Tissue and Favors Fat Deposition

Abstract: Obesity is associated with low-grade inflammation and leukocyte infiltration in white adipose tissue (WAT) and is linked to diabetic complications. Semicarbazide-sensitive amine oxidase, also known as vascular adhesion protein-1 (SSAO/VAP-1), is a membrane protein that is highly expressed in adipocytes and is also present on the endothelial cell surface where it is involved in leukocyte extravasation. We studied fat deposition and leukocyte infiltration in WAT of mice with a null mutation in the amine oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…This ability of BM-HSC to generate WAT immune cells has been demonstrated by injecting BM cells into lethally irradiated mice, suggesting that hematopoietic cells present in WAT are derived from BM [7,8,76]. However, several observations can challenge this view.…”
Section: Adipose Tissue Hematopoietic Stem Cells and Their Potential mentioning
confidence: 87%
“…This ability of BM-HSC to generate WAT immune cells has been demonstrated by injecting BM cells into lethally irradiated mice, suggesting that hematopoietic cells present in WAT are derived from BM [7,8,76]. However, several observations can challenge this view.…”
Section: Adipose Tissue Hematopoietic Stem Cells and Their Potential mentioning
confidence: 87%
“…VAP-1 substrates have been shown to activate glucose transport (59), and feeding mice the SSAO inhibitor semicarbazide limits weight gain and inhibits fat deposition in adipose tissue (60). However, Bour et al demonstrated that Aoc3 -/-animals have reduced leukocyte infiltration into white adipose tissue associated with increased fat deposition, which could not be rescued by expression of VAP-1 from the human adipocyte-specific aP2 promoter (61). These data suggest that the role of VAP-1 in the development of hepatic steatosis is complex and that the effects of adipocyte-specific VAP-1 on the release of adipokines must also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, these immune cells come from other sites, probably the BM via blood circulation. [3][4] Several years ago, we proposed that a population of immature hematopoietic cells able to reconstitute lethally irradiated mice are located in WAT. 5 This hypothesis is consistent with a recent report demonstrating that the bulk of stroma cells host immature hematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%